The Role of Job Control and Coping Strategies as Moderators in the Effect of Emotional Demands on Burnout in Health Workers - Putri, Raissa Safridha; Radikun, Tulus Budi Sulistyo (Universitas Muhammadiyah Metro, 2023)
Health workers have jobs that have a heavy burden. Long and uncertain working hours and patients with various characteristics and diseases cause health workers to have high burnout levels. This study aims to see the role of job control and coping strategies as a moderator in the effect of emotional job demands on burnout. This research is a cross-sectional quantitative study with a sample of 142 health workers. This study uses instruments from the Oldenburg Burnout Inventory, Copenhagen Psychosocial Questionnaire II (COPSOQ II), Copenhagen Psychosocial Questionnaire, and Brief COPE Inventory (Coping Orientation to Problems Experienced). Data processing uses process macro moderation analysis by Andrew F. Hayes through the SPSS Program. The study results show that job control moderates emotional job demands and the exhaustion dimension of burnout. Meanwhile, coping strategies, problem-focused or emotion-focused coping moderates between emotional job demands and the burnout dimension of disengagement. The workplace of health workers can provide job control by the position and work of the workers, which are still within the limits of their authority and responsibility. Health workers can also be given activities or programs that can improve their coping skills, either those that focus on behavior or those that focus on emotions.